Kebangkitan Kembali Tafsir Klasik di Era Kontemporer: Antara Revivalisme, Kontinuitas Epistemologis, dan Stagnasi Intelektual - Ahmad Bahrudin; M. Tohir; Abd Muin; Deshinta Arrova Dewi (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2026)
The persistence of classically oriented Qur'anic exegesis in the contemporary period presents an important yet underexplored phenomenon in Qur'anic studies. While modern tafsir has generally been associated with reformist, contextual, and interdisciplinary approaches, a number of contemporary exegetical works continue to preserve classical interpretive structures and methodologies. This study investigates the re-emergence of classical exegesis through a comparative analysis of three major twentieth-century commentaries: Tafsir al-Munir by Wahbah al-Zuhaili, al-Tahrir wa al-Tanwir by Muhammad al-Tahir Ibn Ashur, and Khawatir Hawl al-Qur'an al-Karim by Muhammad Mutawalli al-Sha'rawi. Employing qualitative library research with descriptive-comparative analysis, the study examines their exegetical methodologies, interpretive sources, systematic structures, and socio-intellectual orientations. The findings demonstrate that all three commentaries preserve essential characteristics of classical tafsir—including the predominance of the tahlili method, extensive engagement with earlier exegetical authorities, philological analysis, and comprehensive verse-by-verse interpretation—while simultaneously incorporating selective responses to contemporary intellectual and social concerns. These findings challenge the conventional binary classification that sharply separates classical and contemporary tafsir. Instead, the study argues that these works represent a form of neo-classical exegesis, characterized by epistemological continuity rather than methodological stagnation. Consequently, the re-emergence of classical exegesis should be understood neither merely as a revivalist movement nor as evidence of intellectual decline, but as a dynamic strategy for preserving the authority of the classical exegetical tradition while negotiating the demands of modernity. This study contributes a new theoretical perspective by proposing neo-classical exegesis as an intermediary category within the historiography of Qur'anic interpretation.